2015
DOI: 10.1016/j.rmed.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Detecting laryngopharyngeal reflux in patients with upper airways symptoms: Symptoms, signs or salivary pepsin?

Abstract: Salivary pepsin may be used as a screening adjunct to supplement the RFS in the clinical workup of patients with extra-oesophageal symptoms and upper respiratory tract presentations of reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
58
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 34 publications
(35 reference statements)
3
58
0
4
Order By: Relevance
“…The pepsin immunoassay has been adapted as a lateral flow–based test (Peptest) with results available within minutes . According to the meta‐analysis performed by Wang et al, diagnostic values of pepsin detection varied markedly in studies involving different study designs . The heterogeneity of the studies included sample size, diagnostic criteria (pH monitoring/symptoms/signs), assay type (Peptest vs. others), timing of the collection of saliva/sputum, number of pepsin tests performed, and pepsin concentration cutoff values among other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pepsin immunoassay has been adapted as a lateral flow–based test (Peptest) with results available within minutes . According to the meta‐analysis performed by Wang et al, diagnostic values of pepsin detection varied markedly in studies involving different study designs . The heterogeneity of the studies included sample size, diagnostic criteria (pH monitoring/symptoms/signs), assay type (Peptest vs. others), timing of the collection of saliva/sputum, number of pepsin tests performed, and pepsin concentration cutoff values among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…23 According to the meta-analysis performed by Wang et al, 24 diagnostic values of pepsin detection varied markedly in studies involving different study designs. [25][26][27][28][29] The heterogeneity of the studies included sample size, diagnostic criteria (pH monitoring/symptoms/signs), assay type (Peptest vs. others), timing of the collection of saliva/sputum, number of pepsin tests performed, and pepsin concentration cutoff values among other factors. The team concluded that current evidence for salivary pepsin use is insufficient, and that further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
“…Gastro‐esophageal reflux is common in infants and children and can be assessed using diagnostic tests such as esophageal pH monitoring and MII/pH . Salivary pepsin has been studied as a potential noninvasive diagnostic method for gastric reflux in adults and children . Because pepsin is normally produced only by gastric chief cells in the stomach and is absent from the oropharynx, the presence of pepsin in the saliva is evidence that a gastro‐esophageal reflux event has reached the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of gastric pepsin 3b (pepsin A‐4) in the oropharynx has been studied as a noninvasive method to detect oropharyngeal reflux in both adults and children . Because pepsin A is normally found only in gastric juice, it has been hypothesized that GER events positively correlate with the presence of oropharyngeal pepsin .…”
mentioning
confidence: 99%
See 1 more Smart Citation